Penyuluhan Pertanian Organik di Kelurahan Malasom Distrik Aimas Kabupaten Sorong-Papua Barat Daya - Ajang Maruapey; Nurlela, Nurlela; Rahma Lakamudi; Rajab Lestaluhu; Ferdinan Nuru (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Organic farming is an alternative that is expected to increase agricultural productivity while maintaining the sustainability of agricultural land and the surrounding environment. The service activity was held in Malasom, Aimas District, Sorong Regency, Southwest Papua Province, in May of 2023. The service activity aims to explore the implementation of organic farming education for farmer groups in Sorong Regency, Southwest Papua. The service method applied to the community and farmer groups is a participatory approach that has the participation of various parties, including the Malasom village government, RT heads, partner farmer groups, and local journalists. The implementation of organic farming socialization and extension activities carried out includes location surveys, presentation of extension materials and discussions, field visits and demonstrations, as well as evaluation and monitoring. The results of this program show that there is an increase in knowledge by applying organic crop cultivation practices on a small scale by making compost and its application to plants and improving the quality of agricultural products, reducing the use of chemical pesticides, and increasing farmers' income.